A case study: writing a Spanish dictionary as a collaborative task among beginner students. Issue 1 (2nd January 2016) - Lopez, Nuria
Abstract : This article reports a small-scale study carried out in a beginners' Spanish class of second year undergraduate students. The purpose of the study was to investigate the effectiveness of a vocabulary task in terms of its impact on vocabulary acquisition, the learners' approach to vocabulary learning and their motivation and engagement. The task consisted of the creation of a Spanish dictionary as a collaborative task. The results indicate that the task enhanced vocabulary acquisition in this course. Positive results were also obtained in relation to the learners' perceived usefulness of the task and to their approach to vocabulary learning. However, the irregular improvement in vocabulary acquisition among learners and some results from the group interviews conducted at the end of the study suggested that although the Dictionary task was generally successful in terms of enhancement of vocabulary acquisition and students' motivation, it nevertheless needs complementing with follow-up vocabulary activities that provide students with further opportunities to recycle the words introduced in the dictionary.